Students’ Perspectives on Feedback From Write & Improve Website in Supporting Writing Skills - Rahmah, Eka Maurina; Ulya, Inayatul (Universitas Pahlawan Tuanku Tambusai, 2025)
Writing is one of important skills considered in the process of learning English. In order to support the development of writing skills, feedback is key features for guiding the English learners in identifying and correcting their writing errors. However, with the advancements of technology, automated writing evaluation (AWE) tool integrated to provide immediate feedback on students’ writing. This study aims to find out whether feedback provided by this website help students to produce written works and help them understand the basic elements of writing and their writing level. English students at Pekalongan University were participant of this study. Data were collected through questionnaire and semi structured interview. The result revealed that students have positive response regarding the use of feedback from Write Improve in supporting their writing skills. However, the website still needs further development.